Assessing conservation of a tropical African estuary : waterbird disturbance, livelihoods, and ecotourism - England, Kate (Percy FitzPatrick Institute of African Ornithology, 2015)
The aim of this study was to evaluate the potential costs and benefits of increasing conservation in the Sabaki River Mouth Important Bird Area. This was achieved by assessing the vulnerability of waterbirds to disturbance from human activity in the estuary, the current use and importance of the area to local livelihoods, and the value (current and potential) of tourism. Waterbird densities and levels of human activity were quantified from 20 September to 25 November 2010 in the intertidal area of the Sabaki River Mouth Important Bird Area on the central Kenyan coast. Household surveys were conducted in the adjacent Sabaki Village from 15 October to 24 November 2010 (N = 190). The current and potential value of ecotourism was investigated by recording visitation rates and interviewing visitors to ascertain their preferences and willingness to pay an entry fee from 5 October to 4 November 2010. Three types of response variables were collected at six sites to characterize relative responses of waterbirds to simulated human disturbances. These were 1) changes in bird density within a 40 m radius of a stationary disturbance (D40); 2) minimum distance of birds from the source of a stationary disturbance (¡Ü 40 m); and 3) the time for 90% of original bird abundance to recover following a mobile human disturbance which caused all birds to flee the immediate vicinity. Disturbance response metrics were estimated from these variables by calculating normalized mean residuals from regressions of density (D40) and minimum approach distance against expected densities measured in the absence of disturbance, for 14 waterbird species.